2013
DOI: 10.1124/mol.113.086702
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Disulfide Bridges Serve Different Purposes in Two Homologous Chemokine Receptors, CCR1 and CCR5

Abstract: In addition to the 7 transmembrane receptor (7TM)-conserved disulfide bridge between transmembrane (TM) helix 3 and extracellular loop (ECL)-2, chemokine receptors (CCR) contain a disulfide bridge between the N terminus and what previously was believed to be ECL-3. Recent crystal and NMR structures of the CXC chemokine receptors (CXCR) CXCR4 and CXCR1, combined with structural analysis of all endogenous chemokine receptors indicate that this chemokine receptor-conserved bridge in fact connects the N terminus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…This domain is generally important for receptor function by contributing to protein folding and conformational constraining in addition to forming the ligand-binding sites (76)(77)(78). ECL-2 is, on average, the longest of the 3 ECLs and encompasses the most divergent loop with sequence variations even within otherwise conserved class A 7TM receptor families (52,79). The length and sequence of ECL-2 are surprisingly conserved for the BILF1 receptors, indicating an essential role of this receptor region.…”
Section: Discussionmentioning
confidence: 99%
“…This domain is generally important for receptor function by contributing to protein folding and conformational constraining in addition to forming the ligand-binding sites (76)(77)(78). ECL-2 is, on average, the longest of the 3 ECLs and encompasses the most divergent loop with sequence variations even within otherwise conserved class A 7TM receptor families (52,79). The length and sequence of ECL-2 are surprisingly conserved for the BILF1 receptors, indicating an essential role of this receptor region.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these studies, small molecule-induced activation (and thereby the ability of the mutant receptors to be activated independently of chemokine binding) was not tested. We recently reported that the disulfide bridges play different roles in the receptors CCR1 and CCR5 (44). In CCR1, the 7TM bridge was found to be essential for activation with both chemokine and small molecule ligands, whereas the CKR bridge was not required for small moleculemediated activation.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines mainly interact with extracellular receptor regions (68), and therefore the two conformationally constraining disulfide bridges have a major impact on chemokine binding (113, 115, 139). Yet, the roles of these bridges vary – even between homologous chemokine receptors like CCR1 and CCR5 (139) and thereby contribute to the explanation for why small drug-like substances act differently on (1) different chemokines for the same receptor (136) or (2) different chemokine receptors (137, 138).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, the roles of these bridges vary – even between homologous chemokine receptors like CCR1 and CCR5 (139) and thereby contribute to the explanation for why small drug-like substances act differently on (1) different chemokines for the same receptor (136) or (2) different chemokine receptors (137, 138). These pharmacodynamic challenges combined with the redundancy of the chemokine system may be central for the lack of success when it comes to the development of anti-inflammatory compounds targeting chemokine receptors.…”
Section: Resultsmentioning
confidence: 99%